Rehabilitation culture and its impact on technology: unpacking practical conditions for ultrabilitation. Issue 11 (21st May 2020) - Boehlen, Wren; Sample, Matthew
Abstract: Purpose: It has been proposed that rehabilitation practice expand its aims beyond recovery to "ultrabilitation, " but only if certain biological, technological, and psychosocial conditions are met. There is thus an opportunity to connect ultrabilitation, as a concept, to adjacent literature on assistive technology and sociotechnical systems. Method: We draw on insights from sociology of technology and responsible innovation, as well as concrete examples of neural devices and the culture of rehabilitation practice, to further refine our understanding of the conditions of possibility for ultrabilitation. Results: "Assistive" technologies can indeed be re-imagined as "ultrabilitative, " but this shift is both psychosocial and technological in nature, such that rehabilitation professionals will likely play a key role in this shift. There is not, however, sufficient evidence to suggest whether they will support or hinder ultrabilitative uses of technology. Conclusion: Advancing the idea and project of ultrabilitation must be grounded in a nuanced understanding of actual rehabilitation practice and the norms of broader society, which can be gained from engaging with adjacent literatures and by conducting further research on technology use in rehabilitation contexts. Implications for rehabilitation: "Assistive" technologies can be conceptually re-imagined as "ultrabilitative" technologies, expanding their utility from recovery to enhancement and flourishing. Actual development and use of ultrabilitative technology is both a technical and psychosocial challenge, and its success depends on the cultural context in which technology is situated. Further empirical research is needed on the ways in which rehabilitation culture and the norms of broader society might impact or even inhibit the use of ultrabilitative technology.